2016
DOI: 10.1016/j.jacc.2015.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Femoral and Carotid Subclinical Atherosclerosis Association With Risk Factors and Coronary Calcium

Abstract: Subclinical atherosclerosis was highly prevalent in this middle-aged male cohort. Association with risk factors and positive CACS was stronger in femoral than carotid arteries. Screening for femoral plaques may be an appealing strategy for improving cardiovascular risk scales and predicting coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
129
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(153 citation statements)
references
References 35 publications
8
129
0
9
Order By: Relevance
“…Many clinical and physiological factors are significantly associated with CAS, including ageing, smoking, hypertension, diabetes. Among them, hypertension is one of the most closely related to CAS [1][2]. Published studies have confirmed that most patients with hypertension have different degrees of CAS [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical and physiological factors are significantly associated with CAS, including ageing, smoking, hypertension, diabetes. Among them, hypertension is one of the most closely related to CAS [1][2]. Published studies have confirmed that most patients with hypertension have different degrees of CAS [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Согласно исследованию AWHS когорты из 1423 чел. в возрасте 40-59 лет наличие АСБ в бедренных артериях ассоциировано с большей частотой и большим уровнем известных факторов риска атеросклероза [40].…”
Section: Ultrasound Markers Of Premanifest Atherosclerosis Of Carotidunclassified
“…Однако в исследовании AWHS наличие АСБ в бедренных артериях в 2,58 раза улуч-шало прогнозирование поражения коронарных арте-рий, оцениваемого с помощью коронарного кальцие-вого индекса [40].…”
Section: Ultrasound Markers Of Premanifest Atherosclerosis Of Carotidunclassified
See 1 more Smart Citation
“…Atherosclerosis is a primary cause of cardiovascular disorders, [1][2][3] and carotid artery stenosis (CS), coronary artery disease (CAD), peripheral artery disease (PAD), and renal artery stenosis (RAS) are representative atherosclerotic diseases. A large-scale cohort study has shown that not only the mortality, but also the incidences of myocardial infarction and cerebral infarction are elevated in patients with such atherosclerotic diseases.…”
Section: Introductionmentioning
confidence: 99%